Effects of Dietary Levels of Vitamin E on Broiler Breeder Performance - Abdul Ghaffar; Abdul Samad; Muhammad Asif Raza; Asghar Abbas; Kashif Hussain; Hafeez Ur Rehman Ali Khera; Muhammad Umair Waqas; Rana Muhammad Shahbakht; Junaid Ali Khan; Atif Rehman (BioScientific Review, 2024)
Background. Broiler breeders can directly affect the production of broiler stock, so their performance is critical. Dietary supplements also play a crucial role in improving their performance. The current study aimed to investigate the impact of vitamin E supplements on broiler breeder performance, including egg production, hatching egg fertility, hatchability, and antibody titer against Newcastle disease and avian influenza.Method. A total of 1500 breeder hens were divided into five groups A, B, C, D, and E. Each group had five (05) replicates. The control group A received no treatment. Group B received 30 mg/kg of vitamin E through feed mixing, Group C received 45 mg/kg; Group D received 60 mg/kg, and Group E received 70 mg/kg of vitamin E through feed mixing. Treatments included two doses of vitamin E (30 and 70 mg/kg) and Zinc-L-selenomethionine and sodium selenite, the two sources of selenium.Results. The current study showed that egg production was not affected by dietary vitamin E levels or sources of vitamin E (p > 0.05). Compared to breeders fed 30mg at 29 weeks, the fertility and hatchability of eggs from breeders fed 70 mg/kg of vitamin E diet was also higher.Conclusion. The outcome of the current trial demonstrates that dietary supplements consisting of vitamin E (70mg/kg feed) and Zinc-L-selenomethionine may improve egg quality and incubation response.